Civil society legitimacy and nuclear non-proliferation - Claudia Kissling (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2008)
During recent years, civil society legitimacy has generated a growing interest in scholarly research. The present article therefore proposes four normative criteria, namely, independence, transparency, participation, and inclusion, in order to start assessing civil society legitimacy empirically. It does so by using the non-proliferation regime as a field of inquiry. In this context, four different advocacy NGOs active during the Nuclear Non-Proliferation Treaty's review processes - MPI, IPPNW, WILPF, and the Friedenswerkstatt - are analysed. The results give a fairly good score for CSO legitimacy, but show that what seems to matter most in this regard is the organizational culture, rather than the organizational structure of an organization. – – In den letzten Jahren hat die Frage zivilgesellschaftlicher Legitimität ein wachsendes Interesse in der Wissenschaft hervorgerufen. Der vorliegende Artikel schlägt daher vier normative Kriterien vor, nämlich Unabhängigkeit, Transparenz, Beteiligung und Inklusion, um zivilgesellschaftliche Legitimität empirisch zu bewerten. Untersuchungsfeld ist das Nichtverbreitungs-Regime. In diesem Zusammenhang werden vier verschiedene, während des Überprüfungsprozesses des Atomwaffensperrvertrages aktive Advocacy-NGOs - MPI, IPPNW, WILPF, und die Friedenswerkstatt - untersucht. Wie das Ergebnis zeigt, schneiden zivilgesellschaftliche Organisationen in ihrer Legitimität relativ gut ab. Allerdings kommt es hierbei mehr auf die Organisationskultur, und weniger auf die Organisationsstruktur einer Organisation an.
Keywords: 300